The impact of effleurage massage on post-exercise physical recovery - Wahyu Hidayat; Roy Januardi Irawan; Soni Sulistyarto; Testa Adi Nugraha (Sriwijaya Journal of Sport, 2025)
Research Problems: Physical recovery is an important aspect in maintaining performance and preventing injuries in athletes. High-intensity training often causes muscle fatigue, decreased fitness, and delayed recovery. Various recovery methods are used to accelerate the return of athletes' physical condition, one of which is sports massage using the effleurage technique. This technique is believed to improve blood circulation, reduce muscle tension, and accelerate the recovery process after training or competition. Research Objectives: This study aims to determine the effect of the effleurage technique on the physical recovery process of Wushu Sanda athletes. Methods: The research design used a pre-experimental one-group pretest-posttest design model with a sample of 10 male athletes aged 15–20 years. Measurements were taken using the Squat Jump test (explosive ability) and Wall Sit test (static muscle endurance). The procedure was carried out over two days, with no treatment (passive rest) on the first day and 12 minutes of effleurage on the second day. Results: The Wilcoxon test results showed a significant improvement in Squat Jump performance (p = 0.005), but no significant improvement in Wall Sit performance (p = 0.114). Conclusion: Effleurage is effective in accelerating dynamic muscle recovery and explosive ability, but is not yet optimal for static muscle endurance. This technique is recommended as part of an athlete's recovery program and may be more effective when combined with other methods such as active stretching or cryotherapy.